HUBUNGAN ANTARA PENGGUNAAN MAJALAH “SUAVE” DAN PEMENUHAN KEBUTUHAN INFORMASI PELANGGAN - Catur Nugroho (Universitas Serang Raya, 2015)
This research entitled “The Relationship Between The Use of Suave Magazine and Fulfillment Information Needs of Customers”.The purpose of this research is to know the relationship between the use of Suave magazine consisting of the intensity of use, the contents of the information, the relationships of individual with the media content, and customers needs of information. With the methods of correlational or eksplanation survey, in this study used the technique of descriptive data analysis and inferential through the hypothesis test of rank Spearman.While to determine the total sample,Slovin formula was used. There are two sources of data in the data collection, that is primary data obtained through poll by means of collecting respondents data magazine Sueve and secondary data obtained through observation and the study of literature.The population of this research is Suave magazine. The theory of uses and gratifications used as the basic theories in this research used to analyze the use of components and component of media effect.Components include the use of media relations, kind of the contents and relationship with the contents that used as the main research. The component of the use of this media can be lowered into three elements, namely the amount of time used in various media, kind of the content being consumed, and the various relations between the individual consumer media with the content being consumed or with the media overall. Theresearch results shows that there are significant relationship between the use of information Suave magazine and meeting the needs of customers. The analysis of this research is able to prove that the use of information Suave magazine can meet the needs of customers, this means that the higher the use of Suave magazine, the higher the meeting the needs of customers information.Meeting the needs of customers to improve information, Suave magazine suggested to more innovative in displaying the content of information. Keywords : use, magazine, uses and gratifications, needs, information.